Strategi Pengembangan Madrasah Di Lembaga Pendidikan (LP) Ma’arif Nahdlatul Ulama Kota Salatiga - M. Gufron (State Institute of Islamic Studies (IAIN) Salatiga, 2012)
This research is intended to know (1) people expectation toward MI Ma’arif NU Salatiga, (2) How is the development strategy in developing MI Ma’arif in order to exist. This research is qualitative by applying natural paradigm. The finding of this reseach shows that the MI Ma’arif is applying arabic and English in daily communication; discipline is the designing is the main factor which is shown by automatic bell in organizing subject and designing additional facilities on multimedia class, changing rooms and toilets, secondly, the school is trying to improve teacher professionalism and management. Finally, the school is trying to build community concern